Effect of High Hydrostatic Pressure Processing on Microbiological Shelf-Life and Quality of Fruits Pretreated with Ascorbic Acid or SnCl(2) - Argyri, Anthoula A. (Hindawi Publishing Corporation, 2014)

(untitled)
In the current study, the processing conditions required for the inactivation of Paenibacillus polymyxa and relevant spoilage microorganisms by high hydrostatic pressure (HHP) treatment on apricot, peach, and pear pieces in sucrose (22°Brix) solution were assessed. Accordingly, the shelf-life was determined by evaluating both the microbiological quality and the sensory characteristics (taste, odor, color, and texture) during refrigerated storage after HHP treatment. The microbiological shelf-life of apricots, peaches, and pears was prolonged in the HHP-treated products in comparison with the untreated ones. In all HHP-treated packages for apricots, peaches, and pears, all populations were below the detection limit of the method (1 log CFU/g) and no growth of microorganisms was observed until the end of storage. Overall, no differences of the L*, a*, or b* value among the untreated and the HHP-treated fruit products were observed up to the time at which the unpressurized product was characterized as spoiled. HHP treatment had no remarkable effect on the firmness of the apricots, peaches, and pears. With regard to the sensory assessment, the panelists marked better scores to HHP-treated products compared to their respective controls, according to taste and total evaluation during storage of fruit products.